Micronutrients, Metabolic Complications, and Inflammation in Ugandan Children With HIV. Issue 5 (May 2020) - Dirajlal-Fargo, Sahera; Shan, Lingpeng; Sattar, Abdus; Kulkarni, Manjusha; Bowman, Emily; Funderburg, Nicholas; Nazzinda, Rashidah; Karungi, Christine; Kityo, Cissy; Musiime, Victor; McComsey, Grace A.
ABSTRACT: Background: Selenium, zinc, and chromium are essential micronutrients. Their alterations have been associated with HIV disease progression, metabolic complications, and mortality. Methods: This is a cross-sectional study in children with perinatally acquired HIV (PHIV, n = 57), HIV-exposed uninfected (HEU, n = 59), and HIV-unexposed uninfected (HIV−, n = 56) children aged 2 to 10 years old, age- and sex-matched, enrolled in Uganda. PHIV were on stable antiretroviral therapy (ART) with undetectable viral load. We measured plasma concentrations of selenium, zinc, and chromium as well as markers of systemic inflammation, monocyte activation, and gut integrity. Results: Among PHIV children, 93% had viral load ⩽20 copies/mL, median CD4 was 37%, and 77% were receiving a nonnucleotide reserve transcriptase regimen. Median age of all participants was 8 years and 55% were girls. Median selenium concentrations were higher in PHIV compared with the HEU and HIV groups ( P < 0.001), 46% of children overall had low zinc status ( P = 0.18 between groups). Higher selenium, but not chromium or zinc, was associated with lower IL6, sTNFRI and II, and higher beta d glucan, a marker of fungal translocation, zonulin, a marker of gut permeability, oxidized LDL and insulin resistance ( P ⩽ 0.01). Conclusion: In this cohort of PHIV on ART in Uganda, there is a high prevalence of low zinc status overall. Higher plasma selenium concentrations were associated with lower systemic inflammation and higher gut integrity markers. Although our findings do not support the use of micronutrient supplementation broadly for PHIV in Uganda, further studies are warranted to assess the role of selenium supplements in attenuating heightened inflammation.